2014
DOI: 10.1093/gbe/evu115
|View full text |Cite
|
Sign up to set email alerts
|

Genes and Junk in Plant Mitochondria—Repair Mechanisms and Selection

Abstract: Plant mitochondrial genomes have very low mutation rates. In contrast, they also rearrange and expand frequently. This is easily understood if DNA repair in genes is accomplished by accurate mechanisms, whereas less accurate mechanisms including nonhomologous end joining or break-induced replication are used in nongenes. An important question is how different mechanisms of repair predominate in coding and noncoding DNA, although one possible mechanism is transcription-coupled repair (TCR). This work tests the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(121 citation statements)
references
References 47 publications
3
118
0
Order By: Relevance
“…In most angiosperms, the opposite is true (Wolfe et al. 1987), possibly owing to RRR mechanisms that are found in plant mtDNA but absent in animals (Christensen 2014). However, in several independent angiosperm lineages, mutation rates in mitochondrial genomes have undergone an acceleration, shifting the mitonuclear mutation balance to a more animal-like pattern (Mower et al.…”
Section: Discussionmentioning
confidence: 99%
“…In most angiosperms, the opposite is true (Wolfe et al. 1987), possibly owing to RRR mechanisms that are found in plant mtDNA but absent in animals (Christensen 2014). However, in several independent angiosperm lineages, mutation rates in mitochondrial genomes have undergone an acceleration, shifting the mitonuclear mutation balance to a more animal-like pattern (Mower et al.…”
Section: Discussionmentioning
confidence: 99%
“…). By comparing mitochondrial genome sequences of Arabidopsis thaliana ecotypes and other closely related angiosperms, Christensen (, ) showed that intergenic sites have a much higher rate of substitution (including insertions/deletions and rearrangements) than synonymous sites, which is a feature that has largely gone unnoticed in previous work. It is not known why substitution rates differ so significantly between these two kinds of so‐called neutral sites, but Christensen (, ) proposed that there is greater selection on synonymous vs. intergenic sites in land plant mtDNAs, which ultimately impacts how these sites are repaired.…”
Section: Do Dna Maintenance Processes Shape Organelle Genome Architecmentioning
confidence: 99%
“…Short‐, micro‐ or nonhomology‐based repair pathways, such as nonhomologous end‐joining or microhomology‐mediated break‐induced replication, are error prone and can often lead to genomic expansion and rearrangements. Figure based on Christensen (, ).…”
Section: Do Dna Maintenance Processes Shape Organelle Genome Architecmentioning
confidence: 99%
“…The mt genomes of angiosperms also fundamentally differ from those of bilaterian animals in that they have much lower rates of nucleotide substitution than the nuclear genome (Wolfe et al 1987), which may be due to mt recombination/repair mechanisms found in plants but not animals (Christensen 2014). However, the slow-plant/fast-animal dichotomy of mt evolution is a gross oversimplification.…”
Section: Introductionmentioning
confidence: 99%